Analisa Faktor-faktor yang Mempengaruhi Transaction Cost pada Holding Period Saham Perusahaan yang Terdaftar di Bursa Efek Jakarta (BEJ) - Yuniningsih, Yuniningsih (Universitas Brawijaya, Indonesia, 2008)
The grade level of Holding Period had been importantly noticed by the stock exchange practicians, both the stock holders and the members of the stock exchange, as one of the company success indicators. Te aim of the research is to find out the influence of Bid-Ask Spread, Market Value and Risk of Return partially and simultaneously to the Holding Period of the cigarette manufacturers that had carried out